Use Of Power Point Media To Improve The Learning Outcomes Of Class 1 Students At SD Negeri 0702 Panyabungan - Ellida Dongoran (STKIP Rokania Pasir Pangaraian, 2022)
This research was conducted with the aim of increasing motivation and learning outcomes of online learning in grade 1 students of SD Negeri 0702 Panyabungan through powerpoint media. This type of research is classroom action research (CAR). The subjects were grade 1 students of SD Negeri 0702 Panyabungan, totaling 23 students. The CAR design uses the Kemmis and McTaggart models which include planning, action, observation, and reflection. Data collection techniques using observation and tests. Data analysis used quantitative and qualitative descriptive statistics. The results showed an increase in learning outcomes, this can be seen from the completeness of the pre-action KKM students and each cycle, namely in the pre-action by 65%. In cycle 1 83% and cycle 2 96%. This was accompanied by an increase in the average student learning outcomes from the actions of 65, cycle 1 was 72.22 and cycle 2 was 82.78. Likewise, the motivation of students from cycle 1 also increased in cycle 2. From the average cycle 1 of 75.5 the category was sufficient in cycle 2 of 89 good categories. Thus, it can be concluded that online learning using power point media can increase student motivation and learning outcomes